LTE for UMTS : Evolution to LTE-Advanced - Holma, Harri (Harri Kalevi), 1970-; Toskala, Antti (Chichester, U. K. : John Wiley & Sons, 2011)
'Still providing the thorough breakdown of the key areas of LTE of the first edition, this new revised edition of LTE for UMTS includes some important new sections on updates to the standards, as well as a look at possible future developments'--Provided by publisher.
'Written by experts actively involved in the 3GPP standards and product development, LTE for UMTS, Second Edition gives a complete and up-to-date overview of Long term Evolution (LTE) in a systematic and clear manner. Building upon on the success of the first edition, LTE for UMTS, Second Edition has been revised to now contain improved coverage of the Release 8 LTE details, including field performance results, transport network, self optimized networks and also covering the enhancements done in 3GPP Release 9. This new edition also provides an outlook to Release 10, including the overview of Release 10 LTE-Advanced technology components which enable reaching data rates beyond 1 Gbps. Key updates for the second edition of LTE for UMTS are focused on the new topics from Release 9 & 10, and include: LTE-Advanced; Self optimized networks (SON); Transport network dimensioning; Measurement results'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Universal Mobile Telecommunications System; Wireless communication systems -- Standards; Mobile communication systems -- Standards; Global system for mobile communications; Long-Term Evolution (Telecommunications)